The development and validation of a work-values scale for vocational high school students. (2018) - Cheng, Po-Wen; Lai, Hui-Min
Work values aid not only in selecting an occupation or job but also in understanding workers' expectations for their ideal job. Thus, work values are extremely important in the career-development process. Research is necessary because vocational high school students enrol on schemes for personal career development as preparation for entering the workplace, and understanding work values should be an essential part of that preparation. A reliable and valid work-values scale for vocational high school students (WVSVS) was developed using data from the Survey Research Data Archive at Taiwanese Academia Sinica. The data were derived from 1, 710 subjects divided into three sample groups of 570. Data from the first sample group was used for exploratory factor analysis, the second for confirmatory factor analysis and the third as a verification sample for cross-validation. The WVSVS was scored for three work values (extrinsic, intrinsic and concomitant values): Extrinsic work values directly describe income, workplace, lifestyle and co-workers; intrinsic work values describe achievement, intellectual stimulation, advancement and interesting work; and concomitant work values explain responsibility, social service and moral values. The WVSVS could be used by teachers for guiding and understanding vocational high school students' work values in preparation for entering the workplace.